Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 6 - Inverse Functions - 6.1 Inverse Functions - 6.1 Exercises - Page 406: 17


(a) $f^{-1}(17)=6.$ (b) $f(2)=3.$

Work Step by Step

Using the definition of the inverse function: $f(x)=y\Leftrightarrow f^{-1}(y)=x$ we get by fillng up the missing gaps: (a) $f(6)=17\Leftrightarrow f^{-1}(17)=6;$ (b) $f(2)=3\Leftrightarrow f^{-1}(3)=2.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.